2018
DOI: 10.1108/afr-08-2017-0066
|View full text |Cite
|
Sign up to set email alerts
|

How do financially vulnerable farms finance debt in periods of falling prices?

Abstract: Purpose The purpose of this paper is to examine the effect of falling commodity prices on farm debt usage of corn and soybean farms, and how this debt usage differs based on the financial leverage of the farm. Design/methodology/approach Using panel data on farms surveyed at least twice in the Agricultural Resource Management Survey (ARMS) from 1996 to 2015, this paper uses a difference-in-differences approach to measure the effect of low commodity price shocks on financially vulnerable farms. To account for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(24 citation statements)
references
References 9 publications
6
18
0
Order By: Relevance
“…The counterfactual analysis suggests particularly high demand for loans when aggregate farm income declines, which suggests the demand for debt capital is counter-cyclical to farm income. The counter-cyclical relationship between farm income and loan demand is consistent with prior findings of income and investment smoothing in the agricultural sector (Whitaker, 2009) and the inverse relationship between income and credit use (Prager, Burns, and Miller, Prager et al;Fiechter and Ifft, 2022).…”
Section: Introductionsupporting
confidence: 86%
“…The counterfactual analysis suggests particularly high demand for loans when aggregate farm income declines, which suggests the demand for debt capital is counter-cyclical to farm income. The counter-cyclical relationship between farm income and loan demand is consistent with prior findings of income and investment smoothing in the agricultural sector (Whitaker, 2009) and the inverse relationship between income and credit use (Prager, Burns, and Miller, Prager et al;Fiechter and Ifft, 2022).…”
Section: Introductionsupporting
confidence: 86%
“…In an analysis of loan data from a major German development bank, Fecke et al (2016) found that loan demand was significantly influenced by the choice of different types of capital investment, loan structures and business climate expectations. In an examination of the effect of declining commodity prices on the use of debt by soybean and corn farmers in the United States, Prager et al (2018) found that, following commodity price shocks, farm businesses with higher debt-to-asset ratios increased their non-real estate debt relative to those with less debt intensive capital structures, while off-farm income reduced reliance on external debt. Aderajew et al (2018) found that earnings volatility, profitability, asset tangibility and growth opportunities were important determinants of farm-level capital structure.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In an examination of the effect of declining commodity prices on the use of debt by soybean and corn farmers in the United States, Prager et al . (2018) found that, following commodity price shocks, farm businesses with higher debt‐to‐asset ratios increased their non‐real estate debt relative to those with less debt intensive capital structures, while off‐farm income reduced reliance on external debt. Aderajew et al .…”
Section: Literature Reviewmentioning
confidence: 99%
“…A declining stock market condition (bearish market) caused by the trade war can be overcome with a healthy balance sheet and financial position (An et al, 2020;Prager, Burns, & Miller, 2018;Takahashi & Yamada, 2021). Policies taken under these conditions play a significant role in companies' survival goals.…”
Section: Determinants Of Corporate Financial Immunitymentioning
confidence: 99%